A low cost instrumentation system to analyze different types of milk adulteration. (May 2015) - Das, Siuli; Sivaramakrishna, Mulinti; Biswas, Karabi; Goswami, Bhaswati
Abstract: In this paper, the design of a complete instrumentation system to detect different types of milk adulteration has been reported. A simple to use indicator type readout device is reported which can be used by milk community people. A low cost microcontroller based automatic sensing system is also reported to detect 'synthetic milk', which has been reconstructed after adulterating the milk with 'liquid-whey'.